The influence of climate change and country-based conflict on crop production: Evidence based on global panel data in the last decade - Rahman, Juli Yandi; Rachmawati, Ro'fah Nur; Nugraha, Arya Muditama; Widjanarko, Farrell Tajusalatin (Universitas Islam Negeri Raden Intan Lampung, 2023)
In the past decade, the food crisis has become a special concern for the international community. This is in the spotlight as the earth ages, increasingly changing climatic conditions lead to erratic crop yields and worsening crop quality. On the other hand, this condition is exacerbated by the increasingly tense dynamics of international politics which leads to conflict between countries. For this reason, we investigated the relationship between these conditions using the linear mixed model method. In this article, the model obtained is able to describe the real conditions currently occurring regarding the relationship between climate change, conflict between countries and crop production. Among other things, it is known that the majority of continents are carrying out agricultural extensions and intensifying efforts to reduce CO2 emissions, to increase crop production. On the other hand, as time goes by, the model shows that environmental temperature fluctuations are getting bigger. Apart from that, conflict factors apparently exacerbate the effects of climate change which directly affects crop production. This article also provides suggestions for countries on a continent to increase crop production while maintaining climate balance.